Balancing Selection Drives the Maintenance of Genetic Variation in Drosophila Antimicrobial Peptides. (4th September 2019) - Chapman, Joanne R; Hill, Tom; Unckless, Robert L
Abstract: Genes involved in immune defense against pathogens provide some of the most well-known examples of both directional and balancing selection. Antimicrobial peptides (AMPs) are innate immune effector genes, playing a key role in pathogen clearance in many species, including Drosophila . Conflicting lines of evidence have suggested that AMPs may be under directional, balancing, or purifying selection. Here, we use both a linear model and control-gene-based approach to show that balancing selection is an important force shaping AMP diversity in Drosophila . In Drosophila melanogaster, this is most clearly observed in ancestral African populations. Furthermore, the signature of balancing selection is even more striking once background selection has been accounted for. Balancing selection also acts on AMPs in Drosophila mauritiana, an isolated island endemic separated from D. melanogaster by about 4 Myr of evolution. This suggests that balancing selection may be broadly acting to maintain adaptive diversity in Drosophila AMPs, as has been found in other taxa.